Number-location bias: do consumers correctly process the number on the product package? - Park, Jihye and Ma, Yoon Jin (Journal of Product & Brand Management, 2019)
Purpose This study aims to investigate the following three issues: whether consumers process numeric information with locational cues, which locations (horizontal vs vertical) are more influential in processing numbers and whether a number-location association is weakened or strengthened when a visual reference frame moves up or down. Design/methodology/approach A field study and a series of three lab experiments were conducted to examine the location effect of numeric information on the package façade on the perceived magnitude of a number. Findings The authors found that a number at the right was perceived as larger than one at the left only when the number is located at the bottom. Also, placing numeric information at the bottom rather than the top of a product package façade was more powerful in processing the numeric information, but this is true only when the visual frame is set lower. Practical implications This study provides practical insights for product managers in placing core numeric information on product packaging to effectively communicate product value to consumers. Optimal locations can be deliberately considered along with types of numeric information and product categories. For healthy products that promote fewer calories, the top area of the package façade may be a better position for placing information on calories per serving to make the product more appealing to those who follow a healthy diet. Heavier, more voluminous products (e.g., refrigerator) better position their volume/weight information at the bottom than at the top or at the right of the bottom than at the left of the bottom on the product facade. Either the left side or right side of the top position may be beneficial for thinner, lightweight products (e.g., television). Originality/value The present work adds valuable empirical findings; inconsistent with past research, left-right location-number associations are not always true. People tend to associate smaller numbers with left-side locations and larger numbers with right-side locations only when the number is located at the bottom. Also, the study reported that top-small, bottom-large associations are not always true. The difference in perceived magnitude of the number between a number at the top and one at the bottom within the visual frame is significant only when the visual frame is set close to the ground.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9qcGJtLTEyLTIwMTctMTcxMQ